Comments on "Design of Controllers with Arbitrary Convergence Time" [Automatica 112 (2020) 108710]. (August 2022) - Orlov, Yury; Krstic, Miroslav
Abstract: The notion of "free-will arbitrary time stability" of (Pal et al. (2020), Definition 4) is ill-posed. The proof of the paper's central result (Pal et al. (2020), Theorem 2) is incomplete. The arbitrary time stability concept (Pal et al. (2020), Definition 3) is implied by prescribed-time stabilization by Song et al. (2017). Additionally, Theorem 1 by Pal et al. (2020) is obtained by a logarithmic change of the Lyapunov function from (Song et al. (2017), Corollary 1).